Chromagraphic Research Of Liniment, Which Active Substance Belongs To New Derivatives Of 1, 2, 4-Triazole - Martynyshyn, V. P.; Hunchak, V. M.; Yaroshenko, А. І.; Parchenko, V. V.; Panasenko, О. І.; Shcherbyna, R. O.; Hunchak, A. V.; Парченко, Володимир Володимирович; Щербина, Роман Олександрович (My University, 2019)
Scientific fact is the relevance of search of new biologically active compounds among derivatives of 1,2,4-triazole [1, 2]. Researchers from different countries demonstrate the efficiency of such exploratory research. The feature of heterocycle system 1,2,4-triazole is not only high reactivity [3], but also low toxicity and biological activity [4]. We should also note the presence of antimicrobial action of some derivatives of 1,2,4-triazole-3-thiols [5].
Keywords: (4-((5-decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine; chromatographic studies; physico-chemical properties